Just and Unjust Warriors : the Moral and Legal Status of Soldiers. - Rodin, David (OUP Oxford, 2008)
Can a soldier be held responsible for fighting in a war that is illegal or unjust? The chapters in the book both challenge and defend many deeply held assumptions: about the liability of soldiers for crimes of aggression, about the nature and justifiability of terrorism, about the relationship between law and morality. - ;Can a soldier be held responsible for fighting in a war that is illegal or unjust? This is the question at the heart of a new debate that has the potential to profoundly change our understanding of the moral and legal status of warriors, wars, and indeed of moral agency itsel.